2021
DOI: 10.1007/s13193-021-01403-8
|View full text |Cite
|
Sign up to set email alerts
|

Elective Surgical Experience During COVID Pandemic at a Tertiary Cancer Care Centre in India: A Retrospective Analysis

Abstract: To analyse and identify possible outcomes of elective cancer surgeries performed at a tertiary cancer centre during COVID19 pandemic. This is a retrospective study including patients that underwent surgery at HCG Manavata cancer centre, Nashik, Maharashtra, India, from 15 March 2020 to 15 June 2020. Among the 458 patients that underwent elective surgeries, 54% were male and 46% were female, with a median age of 50.57 years. The most common sites of cancer distribution were head and neck (24.67%), colorectal (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The timeline included two major peaks and two major nationwide lockdowns. Although some centres reported continuation of the cancer care during the Covid-19 pandemic with outcomes comparable to pre-Covid era, the results were heterogeneous and could not be generalised [ 17 21 ]. Gastrointestinal cancers represent 20% of all the malignancies in India, out of which nearly 20% would need early surgery [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The timeline included two major peaks and two major nationwide lockdowns. Although some centres reported continuation of the cancer care during the Covid-19 pandemic with outcomes comparable to pre-Covid era, the results were heterogeneous and could not be generalised [ 17 21 ]. Gastrointestinal cancers represent 20% of all the malignancies in India, out of which nearly 20% would need early surgery [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The detailed characteristics of the included studies are shown in Table 1 . There were 16 case report [ 16 , 32 , 46 , 48 – 50 , 52 , 54 , 55 , 59 , 66 , 67 , 71 , 75 , 82 , 84 ], 9 case series, 41 cohort [ 8 17 , 23 , 25 , 26 , 29 , 31 , 34 , 43 45 , 51 , 53 , 56 58 , 60 – 65 , 68 70 , 73 , 74 , 77 , 79 , 80 , 83 , 85 ], 2 cross-sectional [ 72 , 76 ] and 1 case–control [ 81 ] studies. These studies were conducted in China ( n = 15), Italy ( n = 8), United States ( n = 6), United Kingdom ( n = 6), Spain ( n = 5), India ( n = 4), France ( n = 3), Turkey ( n = 2), Brazil ( n = 2), Japan ( n = 2), Colombia ( n = 1), Philippines ( n = 1), Poland ( n = 1), Iran ( n = 1), The Netherlands ( n = 1), Belgium ( n = 1), United Arab Emirates ( n = 1), Mexico ( n = 1), Sweden ( n = 1), Austria ( n = 1), Hungary ( n = 1), Australia ( n = 1), and Chile ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Few studies were made within multi-countries ( n = 3) [ 9 , 12 , 51 ]. The majority of the studies were single centre [ 11 , 16 , 23 , 25 , 27 , 28 , 30 – 35 , 44 – 50 , 52 , 54 , 55 , 58 , 59 , 61 – 63 , 65 69 , 71 , 72 , 74 76 , 78 , 80 , 82 – 84 ] and only 25 studies were multi-centre [ 8 10 , 12 – 17 , 26 , 29 , 36 , 43 , 51 , 53 , 56 , 57 , 60 , 64 , 70 , 73 , 77 , 79 , 81 , 85 ]. The median NOS score for these studies was 6 (range, 5–7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some centres reported continuation of the cancer care during the Covid-19 pandemic with outcomes comparable to pre-Covid era, the results were heterogeneous and could not be generalised. [17][18][19][20][21] Gastrointestinal cancers represent 20% of all the malignancies in India, out of which nearly 20% would need early surgery. [22] Moreover, there was about 80% decrease in endoscopic procedures worldwide in the early part of Covid-19 pandemic that seriously impacted the number of newly diagnosed gastrointestinal cases.…”
Section: Introductionmentioning
confidence: 99%